Predictors of Enrolment Intention on Social Media: Guidelines for Universities - Joy Beesoon; Michael C. Cant (Journal of Education Technology, 2023)
Globally, a vast majority higher education institutions are using social media in their day-to-day activities. Consequently, the need for guidelines to effectively use social media in student recruitment has become a necessity as universities compete among themselves. However, guidelines to use social media are scarce, especially in the realm of higher education and student recruitment. This study analyze social media guidelines by determining the predictors of enrolment intention when social media are used during student recruitment. Literature review revealed the existence of five constructs that may be associated with the intention to enrol at a university. A questionnaire was developed and administered to a sample of students from the four public universities. A total of 412 questionnaires were analysed using multiple linear regression and it was found that there are four predictors of enrolment intention, namely social media functionalities, social media engagement, social media content and information needs. From the predictors of enrolment intention and from the descriptive findings of this study, and additional literature, social media guidelines were derived and were recommended to be used by universities during student recruitment.